THE ROLE OF ENERGY IN IRAN-TURKMENISTAN RELATIONS - Ahmad BHAT, Mukhtar (CENTRAL ASIA AND THE CAUCASUS, 2017)
The emergence of independent countries in Central Asia following the Soviet Union’s collapse in 1991 marked a significant turning point in Iran-Turkmenistan relationships. The Islamic Republic of Iran viewed cooperation with independent Turkmenistan as an opportunity to assert its influence in the newly formed Central Asian political landscape and to position itself as a key corridor for energy supplies to other nations. Turkmenistan possesses vast energy resources but lacks direct access to external markets except through Russia. This situation allows Iran to play a crucial role in helping Turkmenistan diversify its energy exports, which is essential for reducing its dependence on the Russian market. Therefore, the main focus of this analysis is the energy-related cooperation between Iran and Turkmenistan, which could not only strengthen bilateral relations but also open a new chapter in their mutual collaboration. Iran’s geostrategic significance is notable; it borders the Gulf of Oman and the Persian Gulf to the south, which are major global energy export centers, while to the north, it shares borders with the Caspian Sea, Armenia, Azerbaijan, and Turkmenistan. To the east, Iran is adjacent to Afghanistan and Pakistan, and in the northwest, it borders Iraq and Turkey. This geographical positioning has positioned Iran as a vital player in regional connectivity, particularly following increased instability in the region after the U.S. military interventions in Afghanistan in 2001 and Iraq in 2003. As a result, Iran is viewed as the most stable and suitable country for Central Asian nations to rely on for connecting their economies with the rest of the world.